EVALUATION OF QUALITY OF LIQUID ORGANIC FERTILIZER FROM RABBIT’S URINE WASTE FERMENTED USING LOCAL MICROORGANISMS AS DECOMPOSERS - & et al., Said (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Rabbit’s urine waste (RUW) is one of the by-products of rabbit metabolism that not utilized. The complex nutrient content of rabbit’s urine is an enormous potential as a basic ingredient of liquid organic fertilizer (LOF). In the production process of LOF, the fermentation process becomes very important. In the fermentation process, the role of decomposer is very important. The use of commercial decomposers (CD) containing selected microorganisms is difficult to implement in rural areas, as they are expensive and difficult to obtain. Therefore, it is very important to find alternative sources of decomposers derived from nature.  This study aims to evaluate the quality of LOF made from RUW using local microorganism (LM) as a decomposer. A total of 3 types of decomposers are applied, namely: 1) feces extract (FE); 2) banana root extract (RBE) and 3) commercial decomposer (CD) as a control. The fermentation process was done for 4 weeks. As many as 3 types of aeration process time (APT) were applied, namely: 1) 0 h; 2) 48 h and 96 h.  The results showed that the differences of APT resulted in pH values; C-Organic levels and C/N ratio of LOF from LUK were different, whereas N-organic and P205 levels were relatively constant.  Different types of decomposers applied in the fermentation process yield different levels of K2O, but the pH value, C-Organic content, C/N ratio and P205 were relatively constant. Performance of CD in LOF fermentation process was no different from FE and RBE performance. Application of both types of decomposers (FE and RBE)was equally potential to replace CD as a decomposer in the production process of LOF. Implementation of APT for 48 h was the best time process than others.